(untitled) (Journal of Educational Sciences, 2018)
In the paper is studying the experience of students’ adaptation with special needs at the Faculty of Philosophy and Political Science of al-Farabi KazNU in pedagogical specialties. The generalization of the experience of educational and upbringing work affects the time interval from 2012 academic year to the present. Directly in the specialties of «Pedagogy and Psychology», «Social Pedagogy and Selfknowledge », more than 300 young specialists were graduated, 4 of them with special needs. Graduates with special needs not only completed a full course in specialties, but also now successfully realize themselves in the society, helping to develop not only to themselves, but to adapt to other pupils who need pedagogical support. As a result of the generalization of experience, a comprehensive concept was developed, how to accompany and facilitate the successful adaptation of students with disabilities in higher school. This concept, through an integrated and systematic approach, includes tools and integrated technologies for the successful adaptation of students at the «risk group»: an inclusive office, technology «Social Modeling», technology «Tutor», technology «Roadmap» («Meeting» form), «Teacher Support» «,» Walking «technology,» Team collaboration «technology,» Consultation «technology, Mobile School technology. In this model, we tested the role of assistant «Tutor» and assistant (volunteer) from fellow classmates. The concept integrates the results of an analysis of the survey of specialists from inclusive educational organizations in Almaty and the positive results of the university’s practice. Key words: inclusions, students with special needs, support technologies, coach technologies.